2001
DOI: 10.1097/00006199-200103000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Heart Rate Variability in Adolescents and Adults With Type I Diabetes

Abstract: Type 1 diabetes is associated with decreased heart rate variability, with the extent of the decrease related to the age of the individual and the severity of the disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 40 publications
2
21
1
1
Order By: Relevance
“…The elevated BMI noted in the minority adolescents with type 2 DM in this study is consistent with the finding of increasing average weight of youth noted in large population studies, such as the National Health and Nutrition Examination Survey IV (Ogden, Flegal, Carroll, & Johnson, 2002). The level of glycemic control for both those with type 1 and type 2 DM in this sample is lower than the 7% glycosylated hemoglobin recommended by the American Diabetes Association (2004) to prevent future cardiovascular disease but is a level frequently seen in adolescents, who tend to exhibit more labile glucose levels (Faulkner et al, 2001;Massin et al, 1999;Wawryk et al, 1997).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The elevated BMI noted in the minority adolescents with type 2 DM in this study is consistent with the finding of increasing average weight of youth noted in large population studies, such as the National Health and Nutrition Examination Survey IV (Ogden, Flegal, Carroll, & Johnson, 2002). The level of glycemic control for both those with type 1 and type 2 DM in this sample is lower than the 7% glycosylated hemoglobin recommended by the American Diabetes Association (2004) to prevent future cardiovascular disease but is a level frequently seen in adolescents, who tend to exhibit more labile glucose levels (Faulkner et al, 2001;Massin et al, 1999;Wawryk et al, 1997).…”
Section: Discussionsupporting
confidence: 90%
“…Earlier research found a negative association between BMI and HRV in adolescents with type 1 DM (Faulkner et al, 2001), and obesity has been suggested as a link to depressed sympathetic and parasympathetic neural modulation (Spallone & Menzinger, 1997). However, more recent findings indicate that obesity is not a confounding factor in autonomic function testing in individuals with diabetes (Maser, 2002).…”
Section: Discussionmentioning
confidence: 97%
“…Impaired HRV is already present in early stages of diabetes [9,11,12]. HRV analysis can detect early subclinical alterations of the autonomic nervous system in children with type 1 diabetes, which seem to consist mainly in a parasympathetic impairment [26].…”
Section: Discussionmentioning
confidence: 99%
“…Nephropathy and cardiovascular dysautonomia are devastating microvascular complications of diabetes that tend to be occur concurrently in adults who experience the ravages of diabetes (Faulkner, Hathaway, Milstead, & Burghen, 2001). Microalbuminuria, a precursor of nephropathy, is associated with cardiovascular complications and mortality in adults with diabetes (Zandbergen et al, 2007).…”
Section: Risks For Microalbuminuria and Decreased Heart Rate Variabilitymentioning
confidence: 99%
“…More recently, the Hoorn Study also found increased mortality in adults with T2DM who had decreased cardiovascular autonomic function (Gerritsen et al, 2000). Within the pediatric literature, heart rate variability (a measure of CV autonomic function) was lower in adolescents with T1DM compared to healthy controls (Boysen, Lewin, Hecker, Leichter, & Uhlemann, 2007; Faulkner et al, 2001) and lower in youth with T2DM versus T1DM (Faulkner, Quinn, L., Rimmer, J. H., & Rich, B. H., 2005). No studies have addressed the concurrent association of lower CV autonomic function and microalbuminuria.…”
Section: Risks For Microalbuminuria and Decreased Heart Rate Variabilitymentioning
confidence: 99%